2009
DOI: 10.1038/sc.2009.70
|View full text |Cite
|
Sign up to set email alerts
|

Acute paraplegia in painless aortic dissection. Rich imaging with poor outcome

Abstract: Study design: Case report. Objective: To describe the clinical and imaging findings of a patient with painless aortic dissection. Setting: University Neurology Department, Thessaloniki, Greece. Patient, Methods, Results: A 46-year-old man was transferred to our Department for emergent evaluation of paraplegia, from the local hospital of the nearby town, where he was admitted complaining from sudden, painless, bilateral leg weakness, 24 h earlier. He presented complete flaccid paraplegia with urinary retention,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The majority of patients presenting with painless AD noticed a sensation of chest pressure, and the symptoms associated with painless AD were diverse, including chest pain, routine health examination, dyspnea, syncope, coma, paralysis, or hemiplegia. In our group of patients, the clinical manifestation of painless AD was variform 2–13 …”
Section: Discussionmentioning
confidence: 72%
“…The majority of patients presenting with painless AD noticed a sensation of chest pressure, and the symptoms associated with painless AD were diverse, including chest pain, routine health examination, dyspnea, syncope, coma, paralysis, or hemiplegia. In our group of patients, the clinical manifestation of painless AD was variform 2–13 …”
Section: Discussionmentioning
confidence: 72%
“…Possible etiologies include in situ thrombosis, aortic saddle embolus, and an intimal flap that causes aortic dissection and thrombosis9,16,19). Aortic dissection and reparative vascular surgery are well-established causes of spinal cord ischemia1,9,10,11,16). Investigations of the relationship between paraplegia and acute aortic thrombosis have suggested that aortic thrombosis may be caused by in situ thrombosis, cancer, chemotherapy ischemic cardiomyopathy13,18,19,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…In the case presented here, the patient did not complain of pain but presented with paraplegia; this is consistent with previous reports of severe neurological complications (such as paraplegia, loss of some or all types of sensation and difficulty in micturition) occurring in patients with AD due to spinal cord ischaemia. 48…”
Section: Discussionmentioning
confidence: 99%